Microfluidic fabrication of lipid nanoparticles for the delivery of nucleic acids - Prakash, Gyan; Shokr, Ahmed; Willemen, Niels; Bashir, Showkeen Muzamil; Shin, Su Ryon; Hassan, Shabir (Advanced drug delivery reviews, 2022)
[Display omitted] Gene therapy has emerged as a potential platform for treating several dreaded and rare diseases that would not have been possible with traditional therapies. Viral vectors have been widely explored as a key platform for gene therapy due to their ability to efficiently transport nucleic acid-based therapeutics into the cells. However, the lack of precision in their delivery has led to several off-target toxicities. As such, various strategies in the form of non-viral gene delivery vehicles have been explored and are currenlty employed in several therapies including the SARS-CoV-2 vaccine. In this review, we discuss the opportunities lipid nanoparticles (LNPs) present for efficient gene delivery. We also discuss various synthesis strategies via microfluidics for high throughput fabrication of non-viral gene delivery vehicles. We conclude with the recent applications and clinical trials of these vehicles for the delivery of different genetic materials such as CRISPR editors and RNA for different medical conditions ranging from cancer to rare diseases.